PENGARUH KONSENTRASI MEDIUM EKSTRAK TAUGE (MET) TERHADAP PERTUMBUHAN Scenedesmus ISOLAT SUBANG - Prihantini, Nining Betawati; Damayanti, Dini; Yuniati, Ratna (Makara Journal of Science, 2007)
The effect of Tauge Extract Medium (TEM) concentration to the growth of Subang isolated Scenedesmus. Research on the effect of several concentration of Tauge Extract Medium (TEM) to Scenedesmus Meyen cell densities was conducted. The research was an experimental study with complete random design with 8 treatments, i.e. 1%, 2%, 3%, 4%, 5%, 6% TEM, aqua bides, and Bold Basal Medium (BBM). The results showed that TEM concentration effected cell densities of Scenedesmus. At peak condition, the highest cell density (3.981.071 sel/mL) was occurred in 4% at the day of seven, and the lowest cell density (87.096 sel/mL) in aqua bides at the day of three. Kruskal-Wallis test showed that there were differences between the mean of cell densities on all treatment media. Multiple comparison test showed that mean of cell numbers of Scenedesmus differed among treatments (p value>0,05) between aqua bides with 1%, 2%, 3%, 4%, 5%, 6%, and BBM.